Pemanfaatan Minyak Jelatah Menjadi Sabun Dalam Rangka Mengurangi Limbah Rumah Tangga Di Desa Gresik - Firra Rosariawari; Aprilia Putri Ningrum; Putri Dwi Yanti; Farah Eka Putri Ramadaniati; Dea Kirana Nurlaili; Risma Indah Salsabila (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Cooking oil is an important basic ingredient in the frying process with the main function as a heat conductor, adding savory taste, increasing nutritional value, and heat of foodstuffs. If cooking oil is used many times it becomes less good for consumption, this is because the fatty acids contained will be more saturated and will change color Used cooking oil that has been used is called used cooking oil. Used cooking oil is oil that has been used more than two or three times frying, and is categorized as waste because it can damage the environment and can cause a number of diseases. So the use of used cooking oil is carried out by reprocessing it for the manufacture of solid soap. The participants of this activity were PKK mothers in one of the villages in Gresik, this activity consisted of discussions, demonstrations and direct practice. The results of this service activity show that community members are very enthusiastic about participating in this activity, as can be seen from the many questions they ask and their desire to participate in this activity. The practice and demonstration are intended to provide skills to the participants in determining the right formula in making laundry soap from used cooking oil. Once these activities take place, it is hoped that the development of the talents they have learned in the future will result in financial rewards.